Photocatalytic Sonogashira reaction over silicon carbide supported Pd–Cu alloy nanoparticles under visible light irradiation. Issue 13 (15th June 2018) - Wang, Bing; Wang, Yingyong; Li, Jiazhou; Guo, Xiaoning; Bai, Gailing; Tong, Xili; Jin, Guoqiang; Guo, Xiangyun
Abstract : PdCu alloy nanoparticles supported on SiC can efficiently catalyze the Sonogashira reaction by visible light irradiation under ligand-free and mild conditions. The superior catalytic activity of PdCu catalysts was caused by the synergistic effect of PdCu alloy nanoparticles. Abstract : The Sonogashira reaction is an important reaction for forming carbon–carbon bonds in organic synthesis, which is typically carried out under harsh reaction conditions. We herein report that PdCu alloy nanoparticles supported on SiC can efficiently catalyze the Sonogashira reaction by visible light irradiation under ligand-free and mild conditions. The addition of Cu enhanced the activity of the PdCu alloy nanoparticles. The Pd3 Cu1 /SiC catalyst exhibited the highest catalytic performance for the Sonogashira reaction of iodobenzene with phenylacetylene, and the conversion of iodobenzene and selectivity of diphenylacetylene were 99.7% and 98.7%, respectively. The Sonogashira reaction catalyzed over the SiC supported PdCu alloy is a light-driven process, and the reaction rate was greatly influenced by the light intensity and wavelength. A possible reaction mechanism for the photocatalytic Sonogashira reaction over Pd3 Cu1 /SiC was proposed.